Factors that contribute to the default of education loan repayment at Tabung Amanah Pendidikan Negeri Melaka / Siti Nur Hazirah Abdul Fattah - Abdul Fattah, Siti Nur Hazirah (2010)
Education loan is one of funds that provided by the government to help the students to pursue in bearing education cost and other expenses. These funds have to be returned after they are graduated. It becomes serious problem when they are facing the difficulty in repayment. According to this problem, this study was done, where the main purpose is to investigate factors that contribute to the default of the education loan repayment. This study was conducted at Tabung Amanah Pendidikan Negeri Melaka (TAPEM).Three variables were developed which are loan interest charged, income level and borrower attitude. Data collected and evidences are being processed by using the SPSS 11.5 Computer program. The researcher also wants to test the hypothesis, which are to investigate the relationship between dependent variable (factors that contribute to the default of education loan repayment) and the independent variable (loan interest charged, income level, and borrowers attitude) that have formulated earlier. Pearson’s Correlation Coefficient was used in order to know the relationship between independent variables (loan interest charged, income level and borrower attitude) and dependent variables (factors that contribute to the default of education loan repayment). From the finding, the result shows that only borrower attitude is the most factors that contribute to the default of education loan repayment. For recommendation, organization should work together with the universities to conduct programs to instill positive attitude toward the loan among students or borrowers. It very important to give their awareness and feel more responsibility to their repayment obligation and it will help other student in the future to pursue their studies.